Transforming the Arts Education Curriculum as a Strategy for Strengthening 21st-Century Competencies: A Comparative Study of Indonesia and Singapore - Ayu Titis Rukmana Sari; Wahyudi Wahyudi (Universitas Nusantara PGRI Kediri, 2026)
Arts education serves to foster students' creativity and visual skills, collaboration, and reflective abilities for the development of 21st-century competencies. Southeast Asian countries use different methods to improve arts education amidst the era of globalization and digital transformation. Singapore emphasizes outcomes aligned with 21st-century competencies (21CC) and systemic support from the education ecosystem, while Indonesia emphasizes local cultural values ​​and character building through the independent curriculum. The purpose of this study is to compare arts education curricula in Indonesia and Singapore with a focus on four main dimensions: philosophy, structure, implementation, and evaluation. This research was conducted through a qualitative approach combined with a comparative study design. Primary data came from official policy documents, such as the Independent Curriculum (Indonesia) and the MOE Arts Syllabus 2024 (Singapore), while secondary data came from scientific literature related to 21st-century arts education. The results show that the philosophy and structure of the curriculum differ significantly. The independent curriculum emphasizes flexibility and local wisdom, allowing for pedagogical innovation, but faces differences in school competency levels. In contrast, Singapore's curriculum is more consistent in its implementation because it is systematic, tiered, and integrated with 21CC, and supported by institutional collaboration and digital technology. Singapore emphasizes authentic assessment, portfolios, and process rubrics, while Indonesia continues to rely on conventional assessments, which can be strengthened with standardized rubrics and teacher training. These findings confirm that alignment between the philosophy, structure, implementation, and assessment of the curriculum determines the effectiveness of arts education in developing 21st-century competencies.